(untitled) (GIST – Education and Learning Research Journal, 2015)
As English has become the language of business, the economy and social media around the world, it is more and more necessary to start teaching English in schools. Countries such as Ecuador have seen the immediate need to review how they prepare teachers of English to meet this new demand. This article shares a reflection on the process of moving from an autonomous university preparation program to a unified approach based on international standards for teachers of English in Ecuador. This transformation is discussed from four perspectives: the US Embassy in Quito that organized the effort; the facilitator who guided the process; the universities that train English teachers and whose programs were to be revised; and the language institutes that provide intensive English instruction to all university students. These last two points of view are provided by two academics that have been part of the group that collaborated in the creation of the proposal. The end result is a new curriculum based on international EFL/ESL teacher standards and, most importantly, created through collaboration among different entities that had not previously worked together.